THE PARADIGM OF CHARACTER EDUCATION IN ISLAMIC ELEMENTARY SCHOOL - Wasehudin, Wasehudin; Wajdi, Muh Barid Nizarudin; Silahuddin, Silahuddin; Syafe'i, Imam; Sirojudin, Rumbang; Bachtiar, Machdum; Hasanah, Uswatun (Universitas Islam Negeri Ar-Raniry, 2024)
This research aims to discuss the important role of teachers as educators and role models in educational institutions, especially in character education at SDIT Al-Izzah Banten. Based on the theoretical framework proposed by Moeslim Abdurrahman, this study emphasizes the importance of role models in character education by underlining the essence of religious teachings that must be applied in everyday life. This study uses a qualitative method with a triangulation technique that combines data from field observations, interviews with teachers and principals, and related literature. This research explores the character education paradigm at SDIT Al-Izzah, emphasizing the importance of acculturating character in the school culture through exemplary behaviour, discipline, habituation, wise advice, and rewards for good behaviour. The research highlights the comprehensive involvement of the school community, including the principal, teachers, administrative staff, caretakers, parents and the local community in creating an environment conducive to character development. Notably, the research revealed the extension of disciplinary practices beyond the classroom, encompassing daily routines such as absences for congregational prayers and communal meals, which contribute to the overall moral formation of students.